<span>jika xy = 0 , kemudian menganggap x dan y = 0
faktor 2x^2-9+7
(2x-2)(x-7)=0
2x-2=0
2x=2
x=1
x-7=0
x=7
</span><span>jika 1 = x1 dan 7 = x2 maka jawabannya adalah 1^2+7^2-4(1)(7)=22
</span>
jika 7 = x1 dan 1 = x2 maka jawabannya adalah
7^2+7^2-4(7)(1)=22
<span>jawabannya adalah 22</span>
Answer:
it is
Step-by-step explanation:
because it addition it doesn't matter which way you put it
Answer:
Slope is 5.
Step-by-step explanation:
y + 3x = 8x -7
y = 5x - 7
coefficient in front of x is the slope/rate of change once you get the equation slope intercept for y = mx + b. m is the slope.
Answer:
<em>1</em><em>)</em><em> </em><em>3</em><em>/</em><em>5</em><em>=</em><em> </em><em>6</em><em>/</em><em>1</em><em>0</em>
<em>2</em><em>)</em><em> </em><em>3</em><em>/</em><em>6</em><em>=</em><em> </em><em>6</em><em>/</em><em>1</em><em>2</em>
<em>3</em><em>)</em><em> </em><em>4</em><em>/</em><em>1</em><em>0</em><em>=</em><em> </em><em>2</em><em>/</em><em>5</em>
<em>4</em><em>)</em><em> </em><em>3</em><em>/</em><em>4</em><em>=</em><em> </em><em>6</em><em>/</em><em>8</em>
<em>5</em><em>)</em><em> </em><em>5</em><em>/</em><em>1</em><em>0</em><em> </em><em>=</em><em> </em><em>1</em><em>/</em><em>2</em>
<em>6</em><em>)</em><em> </em><em>4</em><em>/</em><em>6</em><em>=</em><em> </em><em>8</em><em>/</em><em>1</em><em>2</em>
<em>7</em><em>)</em><em> </em><em>5</em><em>/</em><em>5</em><em>=</em><em> </em><em>1</em><em>0</em><em>/</em><em>1</em><em>0</em>
<em>8</em><em>)</em><em> </em><em>1</em><em>/</em><em>2</em><em>=</em><em> </em><em>6</em><em>/</em><em>1</em><em>2</em>